Requirement analysis for SMART supply chain management for SMEs - Poti Chaopaisarn (2019)
© IEOM Society International. Since the published report of the Industry 4.0 in 2013 by the German National Academy of Science and Engineering, comprehensive researches and developments was provoked in both academia and industry professionals. Researchers tried to conduct exploratory studies of its unforeseen phenomena and practitioners tried to optimize its applications to gain competitive advantages. Along with buzzwords terminologies such as, cloud manufacturing, Internet of Things, cyber-physical systems, augmented reality and artificial intelligence, along with highly anticipated concepts such as SMART factory, SMART manufacturing, SMART warehousing and SMART production, the SMART supply chain was introduced. However, for Small and Medium Enterprises (SMEs), the concept of SMART supply chain is often abstractive and disruptive in nature. Therefore, in this paper, a SSCM implementation model as a conceptual framework in identifying the transitional phases and requirements of SSCM for SMEs was presented. Three transitional phases have been introduced to clarify the adaptation stages for SMEs and its practical implications. Finally, several key benefits of SSCM have been highlighted in this paper, which offers new opportunities for SMEs to compete in the global market and for future research directions.